2000 IEEE International Reliability Physics Symposium Proceedings. 38th Annual (Cat. No.00CH37059)
DOI: 10.1109/relphy.2000.843936
|View full text |Cite
|
Sign up to set email alerts
|

TDDB improvement in Cu metallization under bias stress

Abstract: Time-dependent dielectric breakdown (TDDB) between Cu interconnects is investigated. TDDB lifetime strongly depends on the surface condition of the Cu interconnect and surrounding pTEOS. A NH3-plamsa treatment prior to cap-pSiN deposition on Cu interconnect improved the dielectric breakdown lifetime ( G~) over cap-pSiN deposition only. The plasma treatment also has the beneficial effect of suppressing wiring resistance increase during pSiN deposition. These results suggest that CuO reduction to Cu, and CUN for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Drawbacks of NH 3 plasma treatment NH 3 plasma treatment is widely used to deoxidize native oxides and to nitridize the surface on copper interconnects [10], [11]. However, we show that NH 3 plasma treatment, ether before or after titanium deposition, is not appropriate for contact metallization due to two drawbacks: plasma-induced damage of the gate oxide and excessive nitridation of Ti/TiN.…”
Section: A Disconnection In the Nisi Shared Contactmentioning
confidence: 90%
“…Drawbacks of NH 3 plasma treatment NH 3 plasma treatment is widely used to deoxidize native oxides and to nitridize the surface on copper interconnects [10], [11]. However, we show that NH 3 plasma treatment, ether before or after titanium deposition, is not appropriate for contact metallization due to two drawbacks: plasma-induced damage of the gate oxide and excessive nitridation of Ti/TiN.…”
Section: A Disconnection In the Nisi Shared Contactmentioning
confidence: 90%
“…For example, use of a triangular voltage sweep (TVS) method to characterize Cu ion migration under applied field in dual-damascene via test structures indicated that a low-k/dielectric cap interface may be a fast diffusive pathway [59]. Furthermore, X-ray photoelectron spectroscopy (XPS) analysis showed that NH -plasma was essential in forming a fully nitrided Cu surface prior to SiN barrier capping, reducing and thus eliminating any residual Cu oxide on the Cu trench surface [52], [60].…”
Section: B Concerns Dominated By Interface Defect Control: Time-depementioning
confidence: 99%
“…Furthermore, the test conditions and/or test structures used in evaluating a given metric such as TDDB vary. However, with the advent of a long-term reliability study using TDDB [52], [54], some notions of what constitutes intrinsic reliability in dual-damascene BEOL dielectrics are emerging.…”
Section: B Concerns Dominated By Interface Defect Control: Time-depementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Compared to the Al-alloy, which is easy to perform dry etching process, it is very difficult to manage the Cu dry etching. To realize the Cu interconnect, damascene process with chemical mechanical polishing (CMP) of Cu is widely studied.…”
Section: Introductionmentioning
confidence: 99%